A New Chiral Binaphthalene‐Based Fluorescence Polymer Sensor for the Highly Enantioselective Recognition of Phenylalaninol. Issue 47 (10th October 2013) - Wei, Guo; Zhang, Shuwei; Dai, Chunhui; Quan, Yiwu; Cheng, Yixiang; Zhu, Chengjian
Abstract A new (S)‐binaphthalene‐based polymer (P‐1) was synthesized by the polymerization of 5, 5′‐((2, 5‐dibutoxy‐1, 4‐phenylene)bis(ethyne‐2, 1‐diyl))bis(2‐hydroxy‐3‐(piperidin‐1‐ylmethyl) benzaldehyde (M‐1) with (S)‐2, 2′‐dimethoxy‐(1, 1′‐binaphthalene)‐3, 3′‐diamine (M‐2) through the formation of a Schiff base; the corresponding chiral polymer (P‐2) could be obtained by the reduction of polymer P‐1 with NaBH4. Chiral polymer P‐1 exhibited a remarkable "turn‐on" fluorescence‐enhancement response towards (D)‐phenylalaninol and excellent enantioselective recognition behavior with enantiomeric fluorescence difference ratios (ef) as high as 8.99. More importantly, chiral polymer P‐1 displays a bright blue fluorescence color change upon the addition of (D)‐phenylalaninol under a commercially available UV lamp, which can be clearly observed by the naked eye. On the contrary, chiral polymer P‐2 showed weaker enantioselective fluorescence ability towards the enantiomers of phenylalaninol.